The deselection process in competitive female youth Sport - Neely, K. C.; Dunn, J. G. H.; McHugh, T.-L. F.; Holt, N. L. (The Sport Psychologist, 2016)
The overall purpose of this study was to examine coaches' views on deselecting athletes from competitive female adolescent sport teams. Individual semistructured interviews were conducted with 22 head coaches of Canadian provincial level soccer, basketball, volleyball, and ice hockey teams. Interpretive description methodology (Thorne, 2008) was used. Results revealed deselection was a process that involved four phases: pre-tryout meeting, evaluation and decision-making, communication of deselection, and post deselection reflections. Within the evaluation and decision-making phase coaches made programmed and nonprogrammed decisions under conditions of certainty and uncertainty. When faced with uncertainty coaches relied on intuition.